Writings of Warner Mifflin : forgotten Quaker abolitionist of the revolutionary era - Mifflin, Warner, 1745-1798; Nash, Gary B.; McDowell, Michael R. (Newark : University of Delaware Press, 2021)
In The Writings of Warner Mifflin, Gary Nash and Michael McDowell present the correspondence, petitions, and memorials to state and federal legislative bodies, semi-autobiographical essays, and other materials of the key figure in the U.S. abolitionist movement between the end of the American Revolution and the Jefferson presidency. Virtually unknown to Americans, Mifflin has been brought to life in Nash's recent biography, Warner Mifflin: Unflinching Quaker Abolitionist (2017). This volume provides an array of insights into the mind of this conscience-bound pacifist Quaker who became instrumental in making Kent County, Delaware, a bastion of free blacks liberated from slavery and a seedbed of a reparationist doctrine that insisted that enslavers owed "restitution" to manumitted Africans and their descendants. Mifflin's writings also show how he became the most skilled lobbyist of the antislavery campaigners who haunted the legislative chambers of North Carolina, Virginia, Maryland, Delaware, and Pennsylvania as well as the halls of the Continental Congress and the First and Second Federal Congresses. An opening introduction and introductions to each of the five chronologically arranged parts of the book provide context for the documents and a narrative of the life of this remarkable American.
To James Pemberton, January 16, 1785 -- To James Pemberton, February 16, 1785 -- To John Parrish, August 22, 1785 -- To the General Assembly of the Delaware State~The Memorial and Address of the People Call'd Quakers Inhabitants of This State, December 27, 1785 -- To Daniel Mifflin, June 6, 1786 -- To John Dickinson, August 11, 1786 -- To Governor William Smallwood, August 31, 1786 -- To James Pemberton, December 12, 1786 -- To James Pemberton, February 3, 1787 -- To John Parrish, February 9, 1787 -- To John Parrish, April 30, 1787 -- To Abigail Parrish, May 13, 1787
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (de Gruyter, viewed March 12, 2025).
eBooks on EBSCOhost
Keywords: Mifflin, Warner, -- 1745-1798.; Mifflin, Warner, -- 1745-1798; Quaker abolitionists -- Delaware; Antislavery movements -- United States -- History -- 19th century -- Sources; Abolitionnistes quakers -- Delaware; Mouvements antiesclavagistes -- États-Unis -- Histoire -- 19e siècle -- Sources; Historical; BIOGRAPHY & AUTOBIOGRAPHY; Revolutionary Period (1775-1800); United States; Essays; LITERARY COLLECTIONS; Quaker; Christianity; RELIGION; Antislavery movements; Quaker abolitionists; Delaware; United States; 1800-1899; History; Sources